2007
DOI: 10.1039/b618104j
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll derivatives as visual pigments for super vision in the red

Abstract: The primary event in vision is light-initiated activation of visual pigments. All visual pigments consist of the protein opsin bound to 11-cis-retinal and are responsible for initiating the transformation of light into an electrical signal. In a mouse model, we show that derivatives of chlorophyll can act as visual pigments initiating the transformation of light into an electrical signal and thus change the primary event in vision to initial activation of a chlorophyll derivative. Electroretinographic b-wave a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 35 publications
(20 reference statements)
0
43
1
Order By: Relevance
“…We previously observed that chlorophyll metabolites enabled photonic energy capture to enhance vision using a mouse model (Isayama et al, 2006;Washington et al, 2004;Washington et al, 2007). Because ATP can regulate a broad range of biological processes, we suspect that ATP modulation also played a role in vision enhancement.…”
Section: Atp Stores and Life Spanmentioning
confidence: 99%
“…We previously observed that chlorophyll metabolites enabled photonic energy capture to enhance vision using a mouse model (Isayama et al, 2006;Washington et al, 2004;Washington et al, 2007). Because ATP can regulate a broad range of biological processes, we suspect that ATP modulation also played a role in vision enhancement.…”
Section: Atp Stores and Life Spanmentioning
confidence: 99%
“…In fact, the UV and red-specific visual enhancement we detected in planarians firmly recapitulates the observations in mice from Washington et al . 11 ; as they noticed, wavelengths causing visual gain of function correspond to peaks in the absorption spectrum of Ce 6 . Furthermore, we showed that soaking animals in a Ce 6 -containing solution for a few minutes (see section “Photophobicity assay” in “Methods”) was sufficient to elicit drastic changes in visual perception.…”
Section: Discussionmentioning
confidence: 79%
“…Furthermore, we showed that soaking animals in a Ce 6 -containing solution for a few minutes (see section “Photophobicity assay” in “Methods”) was sufficient to elicit drastic changes in visual perception. Similarly, several groups found that in vertebrate models Ce 6 promptly reaches (within minutes) the ROS, even if the substance is administered systemically 1114 . All in all, Ce 6 seems to have rapid uptake and to cause opsin spectral shift at specific wavelengths in invertebrates as much as in vertebrates.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Perhaps more surprisingly, various chlorophyll-related compounds, such as chlorine e6, will interact with bovine rhodopsin to act as a photosensitizer for long wavelength illumination27, as well as enhancing thermal stability of the visual pigment28. Furthermore, they are also accumulated by isolated salamander rods29 and in the mammalian retina following intravenous injection3031, where they increase sensitivity to longwave illumination. These observations suggest that chlorophyll derivatives become easily incorporated into the retina of many vertebrates and interact with their visual pigments, even those species that do not usually contain such substances.…”
Section: Discussionmentioning
confidence: 99%